Molecular epidemiology and evolution of norovirus in Australia and New Zealand, 2018 to 2020 - Grace J. H. Yan; Joanne Hewitt; Lewis K. Mercer; Emma F. Harding; Dawn Croucher; Alice G. Russo; Peter G. Huntington; Jason M. Mackenzie; William D. Rawlinson; Peter A. White (Infectious Diseases, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Aminoethyl substitution enhances the self-assembly properties of an aminocellulose as a potential archaeological wood consolidant - Jennifer M. K. Wakefield; Robert Hampe; Richard B. Gillis; Agnes Sitterli; Gary G. Adams; Hartmut Kutzke; Thomas Heinze; Stephen E. Harding (European Biophysics Journal, 2020)
The 6-deoxy-6-aminocelluloses—or “aminocelluloses”—are a class of synthetic natural cellulose derivatives which are mostly aqueous soluble and have excellent film-forming properties. Recent studies have connected these properties at the molecular level with protein-like self-associative behaviour for a range of aminocelluloses including a 6-deoxy-6-(ω-aminoethyl) aminocellulose AEA-1 with the association being a two-stage process—a reversible oligomerisation followed by further (semi-reversible) aggregation into larger structures. Here, we synthesise and compare a new 6-deoxy-6-(ω-aminoethyl) aminocellulose AEA-1′ with different degree of substitution with one with further alkyl derivatisation, namely 6-deoxy-6-(ω-hydroxyethyl) aminocellulose HEA-1′. As with AEA-1, sedimentation velocity and sedimentation equilibrium in the analytical ultracentrifuge still show a two-stage process for both AEA-1′ and HEA-1′, with the latter giving higher molar masses. The consequences of these properties for use as consolidants for archaeological wood are considered.

Production of membrane proteins for characterisation of their pheromone-sensing and antimicrobial resistance functions - Aalishaa A. Azam; Jean M. Kinder; G. Nasir Khan; Ade Alase; Pikyee Ma; Yang Liu; James R. Ault; Peter J. F. Henderson; Babur Z. Chowdhry; Bruce D. Alexander; Stephen E. Harding; Mary K. Phillips-Jones (European Biophysics Journal, 2018)

Controlled depolymerisation assessed by analytical ultracentrifugation of low molecular weight chitosan for use in archaeological conservation - Jennifer M. K. Wakefield; Richard B. Gillis; Gary G. Adams; Caitlin M. A. McQueen; Stephen E. Harding (European Biophysics Journal, 2018)

Comparative Biology of Cycad Pollen, Seed and Tissue - A Plant Conservation Perspective - J. Nadarajan; E. E. Benson; P. Xaba; K. Harding; A. Lindstrom; J. Donaldson; C. E. Seal; D. Kamoga; E. M. G. Agoo; N. Li; E. King; H. W. Pritchard (The Botanical Review, 2018)

Fishes in a changing world: learning from the past to promote sustainability of fish populations - T. A. C. Gordon; H. R. Harding; F. K. Clever; I. K. Davidson; W. Davison; D. W. Montgomery; R. C. Weatherhead; F. M. Windsor; J. D. Armstrong; A. Bardonnet; E. Bergman; J. R. Britton; et al. (Journal of Fish Biology, 2018)
Populations of fishes provide valuable services for billions of people, but face diverse and interacting threats that jeopardize their sustainability. Human population growth and intensifying resource use for food, water, energy and goods are compromising fish populations through a variety of mechanisms, including overfishing, habitat degradation and declines in water quality. The important challenges raised by these issues have been recognized and have led to considerable advances over past decades in managing and mitigating threats to fishes worldwide. In this review, we identify the major threats faced by fish populations alongside recent advances that are helping to address these issues. There are very significant efforts worldwide directed towards ensuring a sustainable future for the world's fishes and fisheries and those who rely on them. Although considerable challenges remain, by drawing attention to successful mitigation of threats to fish and fisheries we hope to provide the encouragement and direction that will allow these challenges to be overcome in the future.

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Polymorphism at the avpr1a locus in male prairie voles correlated with genetic but not social monogamy in field populations - N. G. SOLOMON; A. R. RICHMOND; P. A. HARDING; A. FRIES; S. JACQUEMIN; R. L. SCHAEFER; K. E. LUCIA; B. KEANE (Molecular Ecology, 2009)
Integrative studies of genetics, neurobiology and behaviour indicate that polymorphism in specific genes contributes to variation observed in some complex social behaviours. The neuropeptide arginine vasopressin plays an important role in the regulation of a variety of social behaviours, including social attachment of males to females, through its action on the vasopressin 1a receptor (V1aR). In socially monogamous prairie voles ( Microtus ochrogaster ), polymorphism in the length of microsatellite DNA within the regulatory region of the gene ( avpr1a ) encoding the V1aR predicts differences among males in neural expression of V1aRs and partner preference under laboratory conditions. However, understanding the extent to which V1aR mediates variation in prairie vole social and reproductive behaviour observed in nature requires investigating the consequences of avpr1a polymorphism and environmental influences under ecologically relevant conditions. We examined the relationship between avpr1a length polymorphism and monogamy among male prairie voles living in 0.1 ha enclosures during a time similar to their natural lifespan. We found no evidence that avpr1a genotype of males predicts variation in social monogamy measured in the field but some indices of social monogamy were affected by population density. Parentage data indicated that a male’s avpr1a genotype significantly influenced the number of females with which he sired offspring and the total number of offspring sired. Total brain concentrations of V1aR mRNA were not associated with either male behaviour or avpr1a genotype. These data show that melding ecological field studies with neurogenetics can substantially augment our understanding of the effects of genes and environment on social behaviours.

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Larval lobster ( Homarus americanus ) distribution and drift in the vicinity of the Gulf of Maine offshore banks and their probable origins - G. C. HARDING; K. F. DRINKWATER; C. G. HANNAH; J. D. PRINGLE; J. PRENA; J. W. LODER; S. PEARRE; W. P. VASS (Fisheries Oceanography, 2005)
Surveys for lobster larvae in offshore waters of the north‐eastern Gulf of Maine in 1983, 1987 and 1989 confirm that local hatching occurs mainly at depths

Incidence and distribution of viruses of Taro ( Colocasia esculenta ) in Pacific Island countries - P. A. Revill; G. V. H. Jackson; G. J. Hafner; I. Yang; M. K. Maino; M. L. Dowling; L. C. Devitt; J. L. Dale; R. M. Harding (Australasian Plant Pathology, 2005)

Sugarcane bacilliform virus encapsidates genome concatamers and does not appear to integrate into the Saccharum officinarum genome - R. J. Geijskes; K. S. Braithwaite; G. R. Smith; J. L. Dale; R. M. Harding (Archives of Virology, 2004)

Measurement of the skin microcirculation through intact bandages using laser Doppler flowmetry - J. M. Melhuish; L. Krishnamoorthy; T. Bethaves; M. Clark; R. J. Williams; K. G. Harding (Medical & Biological Engineering & Computing, 2004)

A promoter derived from taro bacilliform badnavirus drives strong expression in transgenic banana and tobacco plants - I. C. Yang; J. P. Iommarini; D. K. Becker; G. J. Hafner; J. L. Dale; R. M. Harding (Plant Cell Reports, 2003)

Sequence analysis of an Australian isolate of sugarcane bacilliform badnavirus - R. J. Geijskes; K. S. Braithwaite; J. L. Dale; R. M. Harding; G. R. Smith (Archives of Virology, 2002)

The Scientific Foundations of Habitat Conservation Plans: a Quantitative Assessment - Elaine K. Harding; Elizabeth E. Crone; Bret D. Elderd; Jonathan M. Hoekstra; Alexa J. McKerrow; John D. Perrine; Jim Regetz; Leslie J. Rissler; Amanda G. Stanley; Eric L. Walters; Nceas Habitat Conservation Plan Working Group (Conservation Biology, 2001)
The number of habitat conservation plans ( HCP) has risen dramatically since the first plan was written over 18 years ago. Until recently, no studies have quantitatively investigated the scientific foundations underlying these documents. As part of a larger study of HCPs, we examined 43 plans primarily to assess the availability and use of scientific data and secondarily to determine the extent of involvement by, and influence of, independent scientists within the process. Specifically, our analysis focused on five key steps taken when an HCP is developed: assessing status of a species, determining take, predicting the project effects, mitigating for those effects, and monitoring of take and mitigation. In general, we found that the preparers of HCPs utilized existing scientific information fairly well, with 60% of plans not missing any available information described by our study as “starkly necessary.” The most common types of underutilized available data included those describing the influence of stochastic processes and habitat quality or quantity on species persistence. For many species, however, data on biology or status simply did not exist, as demonstrated by the fact that we could locate quantitative population estimates for only 10% of the species. Furthermore, for 42% of the species examined we had insufficient data and analysis to determine clearly how predicted take might affect the population. In many cases, mitigation measures proposed to offset take frequently addressed the most important local threats to the species with moderately reliable strategies. Species with monitoring programs rated as sufficient had plans that proposed to collect a greater amount of “quantitative” data than did those programs rated insufficient. Finally, when species “experts” were consulted, plan quality was generally higher. Overall, available scientific information in a majority of categories was fairly well utilized, but for many species additional studies and more in‐depth analyses were required to provide adequate support for issuance of an incidental take permit.

Interactive image processing system for assessment of cell movement - A. Hoppe; D. Wertheim; W. G. Jiang; R. Williams; K. Harding (Medical & Biological Engineering & Computing, 1999)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Mapping of the gene encoding the B56β subunit of protein phosphatase 2A (PPP2R5B) to a 0.5-Mb region of chromosome 11q13 and its exclusion as a candidate gene for multiple endocrine neoplasia type 1 (MEN1) - S. A. Forbes; A. A. J. Pannett; J. H. D. Bassett; B. Harding; C. Wooding; R. V. Thakker; R. Butler; D. Ogilvie; R. Anand; P. Gaudray; G. Weber; C. Larsson; et al. (Human Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Handwipe sampling and analysis procedure for the measurement of dermal contact with pesticides - P. W. Geno; D. E. Camann; H. J. Harding; K. Villalobos; R. G. Lewis (Archives of Environmental Contamination and Toxicology, 1996)

Expression, purification, and use as an antigen of recombinant sugarcane mosaic virus coat protein - G. R. Smith; R. Ford; J. D. Bryant; R. L. Gambley; T. K. McGhie; R. M. Harding; J. L. Dale (Archives of Virology, 1995)